Continuous flow nitration of salicylic acid - Kulkarni, Amol A.; Nivangune, Nayana T.; Kalyani, Vishwanath S.; Joshi, Ramesh A.; Joshi, Rohini R. (Organic Process Research & Development, 2008)
Continuous flow nitration of salicylic acid using HNO3/AcOH was studied in the SS316 tubular microreactor. At specific reaction conditions, complete conversion of the reactant was achieved in less than 7 min. It yielded only mononitro derivatives with a higher selectivity of 5-nitrosalicylic acid. Presence of the lower amount of acetic acid in the reaction mixture was seen to be detrimental, leading to precipitation of the desired product (5-nitrosalicylic acid). Reaction at higher temperatures yielded byproducts. The continuous mode operation using the system comprising the microdevices was demonstrated for 2 h with consistent composition at the outlet.

Catalytic synthesis of chalcone and flavanone using Zn-Al hydrotalcite adhere ionic liquid - Kunde, Lalita B.; Gade, Swapna M.; Kalyani, Vishwanath S.; Gupte, Sunil P. (Catalysis Communications, 2009)
The Claisen-Schmidt condensation of 2'-hydroxy acetophenone and benzaldehyde to chalcone and flavanone show that calcined Zn-Al (6) hydrotalcite is active for this synthesis. Coating of ionic liquid `1-(tri-ethoxy-silyl-propyl)-3-methyl-imidazolium chloride' on Zn-Al hydrotalcites was accomplished employing incipient wetness process and on NaY, NaX, MK-5 and silica gel employing co-condensation methodology. Impregnated IL on calcined Zn-Al (6) catalysts were characterized by XRD, SEM, BET, (13)C and (27)Al NMR analysis and the activity of these catalysts were investigated for chalcone and flavanone synthesis. (27)Al CP MAS NMR technique was used to show that interaction of IL with hydrotalcite modifies the acid-base sites and is responsible for enhancement of catalyst activity. Several aromatic aldehydes were screened to assess the general applicability of the system. (c) 2009 Published by Elsevier B.V.
Keywords: (27)Al CP MAS NMR; chalcone; Claisen-Schmidt condensation; Flavanone; Ionic liquid; Zn-Al hydrotalcite

Continuous flow nitration of benzaldehyde - Kulkarni, Amol A.; Kalyani, Vishwanath S.; Joshi, Ramesh A.; Joshi, Rohini R. (Organic Process Research & Development, 2009)
The nitration of benzaldebyde can be carried out in a safe manner in continuous mode using a microreactor system. Choice of a micromixer was seen to affect the performance of this two-phase reaction significantly The reaction time could he brought down to 2 min by increasing the reaction temperature and thereby taking advantage of higher heat transfer area. The simple T-micromixer is seen to be inefficient for two-phase reactions. Further scope of process intensification is also discussed.

Two-phase flow in minichannels: hydrodynamics, pressure drop, and residence time distribution - Kulkarni, A. A.; Kalyani, Vishwanath S. (Industrial & Engineering Chemistry Research, 2009)
Two-phase flow in mini-channels (1 mm x 1.5 mm x 430 mm and 1.5 mm x 0.5 mm x 430 mm serpentine channel geometry) made in different materials (SS 316, PMMA and Teflon) was studied at different flow rate ratio (0.66, 1.0 and 1.56) of the two immiscible fluids. A dual syringe pump was used to pump the fluids (air-water and water-kerosene) through the channels. For characterization of the two phase flow, experiments were carried out to measure the slug size distribution and relevant hydrodynamic properties, pressure drop across a single serpentine unit (i.e., one sinusoidal unit that includes two 180 degrees return bends connected by a straight portion of 20 mm) and also the residence time distribution of water. In all the cases, the effect of material of fabrication on the hydrodynamics was significant. Apart from flow rates and flow rate ratio of the two fluids, the slug size distribution was seen to have a strong effect of the channel orientation (vertical, horizontal) and also the flow direction (up-flow and down-flow). In the RTD studies, the response curve observed at the end of the channel was significantly different than the published literature. The reasons for such observations are discussed in detail.

Dibutyltin oxide catalyzed aminolysis of oxalate to carbamate, oxamate and derivatives of imidazolidine trione - Kunde, Lalita B.; Kalyani, Vishwanath S.; Gupte, Sunil P. (Applied Organometallic Chemistry, 2010)
Catalytic aminolysis of oxalates by simple and substituted ureas has been shown to give carbamates, oxamates and derivatives of imidazolidine trione. Various substituted ureas and oxalates were screened to verify the applicability of the protocol. The role of dibutyltin oxide as catalyst, effect of solvent and reaction conditions on product distribution pattern has been discussed. Copyright (C) 2010 John Wiley & Sons, Ltd.
Keywords: Aminolysis; carbamate; derivative of imidazolidine trione; oxalate; oxamate; transfunctionalyzation; Urea